Expected Returns to Crime and Crime Location - Nils Braakmann; Arnaud Chevalier; Tanya Wilson (Institute of Labor Economics (IZA), 2022)
We provide first evidence that temporal variations in the expected returns to crime affect the location of property crime. Our identification strategy relies on the widely-held perception in the UK that households of South Asian descent store gold jewellery at home. Price movements on the international market for gold exogenously affect the expected gains from burgling these households, which become relatively more lucrative targets as the gold price increases. Using a neighbourhood-level panel on reported crime and difference-in-differences, we find that burglaries in South Asian neighbourhoods are more sensitive to variations in the gold price than other neighbourhoods in the same municipality, confirming that burglars react rationally to variations in the expected returns to their activities. We conduct a battery of tests on neighbourhood and individual data to eliminate alternative explanations.
Keywords: K42; J19; 330; crime; gold prices; returns to crime; Becker-model; optimal foraging theory; criminal behaviour; crime location